2019
DOI: 10.1111/ppl.13038
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous 5‐aminolevulinic acid improves strawberry tolerance to osmotic stress and its possible mechanisms

Abstract: Cultivated strawberry, one of the major fruit crops worldwide, is an evergreen plant with shallow root system, and thus sensitive to environmental changes, including drought stress. To investigate the effect of 5-aminolevulinic acid (ALA), a new environment-friendly plant growth regulator, on strawberry drought tolerance and its possible mechanisms, we treated strawberry (Fragaria × annanasa Duch. cv. 'Benihoppe') with 15% polyethylene glycol 6000 to simulate osmotic stress with or without 10 mg l −1 ALA. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 41 publications
6
45
0
Order By: Relevance
“…In the present study, after 7 days of treatment, leaves of drought‐treated plants were wilted and the shoot biomass decreased along with the leaf gas exchange attributes (Pn, Tr, Gs, and Ci) and RWC, suggesting that drought stress causes cell dehydration and plant growth reduction. These findings correspond to previous studies in different crop plants under water stress (Cai et al, 2020; Liang et al, 2020; Terletskaya et al, 2020). Drought stress treatment significantly tempered the leaf gas exchange parameters (Pn, Gs, and Tr), while considerable reductions in Pn and Gs were observed in the sensitive cultivar (GY605) upon drought stress compared to control (Table 1), which correspond to previous studies on drought stress (Demirel et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, after 7 days of treatment, leaves of drought‐treated plants were wilted and the shoot biomass decreased along with the leaf gas exchange attributes (Pn, Tr, Gs, and Ci) and RWC, suggesting that drought stress causes cell dehydration and plant growth reduction. These findings correspond to previous studies in different crop plants under water stress (Cai et al, 2020; Liang et al, 2020; Terletskaya et al, 2020). Drought stress treatment significantly tempered the leaf gas exchange parameters (Pn, Gs, and Tr), while considerable reductions in Pn and Gs were observed in the sensitive cultivar (GY605) upon drought stress compared to control (Table 1), which correspond to previous studies on drought stress (Demirel et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Never attention had been payed to different responses of H 2 O 2 between shoots and roots [7] until Wu et al, who found that salt stress induced H 2 O 2 increase in both leaves and roots, and ALA induced more H 2 O 2 increase in roots but depressed in leaves [25]. The tissue-speci c response is con rmed recently [53] and observed in present work once again (Fig. 4), which may be an important characteristic for ALA to induce plant stress tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…In cucumber seedlings, significantly enhanced activities of SOD, POD, CAT, APX (Ascorbate peroxidase), and GR (Glutathione reductase), and reduced ROS and MDA accumulation, are observed under ALA treatment combined with low-temperature stress [10]. Previous studies have reported that ALA activates the plant defense system and defense-related genes, such as genes encoding SOD, POD, CAT, and APX, in rice and strawberry under osmotic and photodynamic stresses and reduce overproduction of ROS and MDA [31][32][33]. ALA is a precursor of heme biosynthesis, and CAT, POD, and APX contain a heme prosthetic group [14], which might be the reason that antioxidant enzyme activities were stimulated in ALA-treated seedlings ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%